Implementing six sigma : smarter solutions using statistical methods - Breyfogle, Forrest W., 1946- (Hoboken, NJ : Wiley, 2003)
* Includes new and expanded coverage of Six Sigma infrastructure building and benchmarking. * Provides plans, checklists, metrics, and pitfalls.
pt. I. S[superscript 4]/IEE Deployment and Define Phase from DMAIC -- 1. Six Sigma Overview and S[superscript 4]/IEE Implementation -- 2. Voice of the Customer and the S[superscript 4]/IEE Define Phase -- pt. II. S[superscript 4]/IEE Measure Phase from DMAIC -- 3. Measurements and the S[superscript 4]/IEE Measure Phase -- 4. Process Flowcharting/Process Mapping -- 5. Basic Tools -- 6. Probability -- 7. Overview of Distributions and Statistical Processes -- 8. Probability and Hazard Plotting -- 9. Six Sigma Measurements -- 10. Basic Control Charts -- 11. Process Capability and Process Performance Metrics -- 12. Measurement Systems Analysis -- 13. Cause-and-Effect Matrix and Quality Function Deployment -- 14. FMEA -- pt. III. S[superscript 4]/IEE Analyze Phase from DMAIC (or Passive Analysis Phase) -- 15. Visualization of Data -- 16. Confidence Intervals and Hypothesis Tests -- 17. Inferences: Continuous Response -- 18. Inferences: Attribute (Pass/Fail) Response -- 19. Comparison Tests: Continuous Response -- 20. Comparison Tests: Attribute (Pass/Fail) Response -- 21. Bootstrapping -- 22. Variance Components -- 23. Correlation and Simple Linear Regression -- 24. Single-Factor (One-Way) Analysis of Variance (ANOVA) and Analysis of Means (ANOM) -- 25. Two-Factor (Two-Way) Analysis of Variance -- 26. Multiple Regression, Logistic Regression, and Indicator Variables -- pt. IV. S[superscript 4]/IEE Improve Phase from DMAIC (or Proactive Testing Phase) -- 27. Benefiting from Design of Experiments (DOE) -- 28. Understanding the Creation of Full and Fractional Factorial 2[superscript k] DOEs -- 29. Planning 2[superscript k] DOEs -- 30. Design and Analysis of 2[superscript k] DOEs -- 31. Other DOE Considerations -- 32. Robust DOE -- 33. Response Surface Methodology -- pt. V. S[superscript 4]/IEE Control Phase from DMAIC and Application Examples -- 34. Short-Run and Target Control Charts -- 35. Control Charting Alternatives -- 36. Exponentially Weighted Moving Average (EWMA) and Engineering Process Control (EPC) -- 37. Pre-control Charts -- 38. Control Plan, Poka-yoke, Realistic Tolerancing, and Project Completion -- 39. Reliability Testing/Assessment: Overview -- 40. Reliability Testing/Assessment: Repairable System -- 41. Reliability Testing/Assessment: Nonrepairable Devices -- 42. Pass/Fail Functional Testing -- 43. S[superscript 4]/IEE Application Examples -- pt. VI. S[superscript 4]/IEE Lean and Theory of Constraints -- 44. Lean and Its Integration with S[superscript 4]/IEE -- 45. Integration of Theory of Constraints (TOC) in S[superscript 4]/IEE -- pt. VII. DFSS and 21-Step Integration of the Tools -- 46. Manufacturing Applications and a 21-Step Integration of the Tools -- 47. Service/Transactional Applications and a 21-Step Integration of the Tools -- 48. DFSS Overview and Tools -- 49. Product DFSS -- 50. Process DFSS -- pt. VIII. Management of Infrastructure and Team Execution -- 51. Change Management -- 52. Project Management and Financial Analysis -- 53. Team Effectiveness -- 54. Creativity -- 55. Alignment of Management Initiatives and Strategies with S[superscript 4]/IEE -- App. A. Supplemental Information -- App. B. Equations for the Distributions -- App. C. Mathematical Relationships -- App. D. DOE Supplement.
Includes bibliographical references (pages 1125-1138) and index.
Keywords: Quality control -- Statistical methods; Έλεγχος ποιότητας -- Στατιστικές μέθοδοι; Production management -- Statistical methods; Production management -- Statistical methods; Quality control -- Statistical methods